2022
DOI: 10.3390/toxics10070393
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterial Ecotoxicology in the Terrestrial and Aquatic Environment: A Systematic Review

Abstract: This systematic review analyzes the studies available on the ecotoxicity of nanomaterials (NMs) in the environment to understand where future research should be addressed for achieving Agenda 2030 goals on sustainable development and environmental safety. We discuss the status of NMs ecotoxicological effects across different organisms that are representative of all natural environments (land, air, water). A total of 1562 publications were retrieved from the Web of Science (all databases) by using the search cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The ecotoxicity assessments using invertebrate animals had mainly been conducted on crustaceans (e.g., Daphnia magna) exposed to graphene oxide [46]. In these studies, the survival and reproduction rates were mainly investigated, while the moulting rate, enzyme activities, and gene expression were less often investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ecotoxicity assessments using invertebrate animals had mainly been conducted on crustaceans (e.g., Daphnia magna) exposed to graphene oxide [46]. In these studies, the survival and reproduction rates were mainly investigated, while the moulting rate, enzyme activities, and gene expression were less often investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding bacteria, most of the studies assessed the effects of NMs in terms of bacterial growth, enzymatic activity, metabolism (e.g., denitrification, nitrification, and respiration), and gene expression [46]. We investigated how the applied nGOs affected bacterial growth, enzymatic activity, and gene expression in two bacterial test systems by measuring Aliivibrio fischeri bioluminescence intensity and Escherichia coli growth and enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Reports show that the total output of nanometer materials in the world is 260,000~309,000 tons, and 63~91% of these materials are discarded in landfills [1]. Previous studies have proven that nanoparticles pose a serious risk to the environment [2][3][4]. Barlaz et al [5] and Khan et al [6] found that nanoparticles could be transported into the interior of landfills, and this aggravated the pollution of nanometer particles.…”
Section: Introductionmentioning
confidence: 99%
“…According to Table 1 , the classical methods for the synthesis of NMs require operator skill, are expensive, and not fully understanding the modeling factors during synthesis can result in unstable NMs with environmental issues, toxic properties, and bioaccumulative behavior [ 20 ]. Subsequently, the use of NMs in different applications can cause serious problems in ecosystems, especially the marine environment, due to the release of nanoproducts in sewage sludge and industrial waste [ 21 , 22 ]. Over the past several years, green synthesis has grown in popularity for the research and development of NMs as a means of addressing the environmental sustainability concerns of the conventional approaches [ 23 ].…”
Section: Introductionmentioning
confidence: 99%